MICROPALEONTOLOGY AND CULTURAL HERITAGE: THE STONE CLADDING MATERIALS OF THE RELIGIOUS BUILDINGS OF PRATO (TUSCANY-ITALY) - Miniati, Francesco; Rescic, Silvia; Sacchi, Barbara; Fratini, Fabio (Ofioliti, 2025)
Microfossils are a group of small size fossil organisms commonly used by geologists in relative age determination and paleoenvironmental reconstructions. More recently, micropaleontology has found applications as an archaeometric tool in the field of archaeology and architecture providing a minimally invasive method for the study of artifacts and building phases. The purpose of this paper is to apply micropaleontological analyses of calcareous nannofossils and calpionellids assemblages to establish the provenance of carbonate lithotypes widely used as ashlars in religious buildings of Prato. The monumental architecture of Prato extensively used a local limestone, the Pietra Alberese. It is a grey marly limestone, which upon exposure to atmospheric agents, becomes whitish or it takes on a brownish colour. This brownish chromatic alteration is found distributed both randomly in isolated ashlars but also appears in linear patterns, particularly in religious buildings. Materials taken from the façade of San Francesco Church in Prato document that the different pattern of alteration arises from the use of two different calcareous lithotypes, namely Pietra Alberese (Eocene) and Calpionella Limestone (Lower Cretaceous). The Pietra Alberese sometimes suffers an ochre colour of alteration, powder to the touch and the altered ashlars show a random distribution on San Francesco Church façade, while Calpionella Limestone regularly suffers of ochre colour of alteration, not powdery to the touch, and is distributed according to a linear pattern.